A Quantitative Analysis of the Reduction Kinetics Involved in the Synthesis of Au@Pd Concave Nanocubes. Issue 71 (21st November 2019) - Xie, Minghao; Zhou, Shan; Zhu, Jiawei; Lyu, Zhiheng; Chen, Ruhui; Xia, Younan
Abstract: Surface capping has been shown to play a pivotal role in controlling the evolution of metal nanocrystals into different shapes or morphologies. With the synthesis of Au@Pd concave nanocubes as an example, here we demonstrate that the capping agent can also impact the reduction kinetics of a precursor, and thereby its reduction pathway, for the formation of metal nanocrystals with distinct morphologies. A typical synthesis involves the reduction of a Pd II precursor by ascorbic acid at room temperature in the presence of Au nanospheres as seeds, together with the use of hexadecyltrimethylammonium chloride (CTAC) or hexadecyltrimethylammonium bromide (CTAB) as the capping agent. In the case of CTAC, the Pd II precursor prevails as PdCl4 2−, leading to the formation of Au@Pd concave nanocubes with a rough surface because of the fast reduction kinetics and thus the dominance of solution reduction pathway. When switched to CTAB, the Pd II precursor changes to PdBr4 2− that features slow reduction kinetics and surface reduction pathway. Accordingly, the Au@Pd concave nanocubes take a smooth surface. This work demonstrates that both reduction kinetics and surface capping play important roles in controlling the morphology of metal nanocrystals and these two roles are often coupled to each other. Abstract : Not just a cap ! The role played by the capping agent in controlling the reduction kinetics of a Pd II precursor for the formation of Au@Pd concave nanocubes with distinctive shapes or morphologies was systematically studied. It is shown that the capping agent can impact the reduction kinetics of a precursor, and thereby its reduction pathway, for the formation of metal nanocrystals with distinct morphologies (see figure).